The Training of Digital Marketing, Business Management and Processing of Used Cooking Oil into Aromatherapy Candles for the Komuninas Wanita Pengumpul Jelantah (KWPJ) Dharmasraya: Pelatihan Digital Marketing, Manajemen Usaha dan Pengolahan Minyak Goreng Bekas menjadi Lilin Aromaterapi terhadap Komunitas Wanita Pengumpul Jelantah (KWPJ) Dharmasraya - Aprimadedi Aprimadedi; Muhammad Hendra; Elinda Revita; Desmi Ofrita; Dandi Rahmatullah (The Future of Education Journal, 2025)
There are three main problems experienced by partners as a result of the urgency of this community service. The first problem is in the area of ​​production. Currently, the used cooking oil collected by partners is not immediately produced into products with economic value. The second problem is related to business management. In the current condition, partners have not yet maintained structured bookkeeping records. The third problem experienced by partners is from the marketing aspect. After being provided with intensive mentoring in the form of IPTEK (Science and Technology) applications and assistance in processing innovation through structured training to improve partners' skills in converting used cooking oil into products with economic value such as aromatherapy candles. Meanwhile, to address the problem of business management where partners have not maintained structured bookkeeping in recording capital, profits, and income, this community service provides a concrete solution in the form of mentoring and training related to business management, primarily on automatic bookkeeping using Microsoft Excel. In terms of marketing issues, for the upstream marketing issue where partners still receive limited used cooking oil with a maximum of 527 liters/4 months. Therefore, this service provides a concrete solution in the form of providing competent digital marketing training and marketing methods to partners, both through in-person outreach and digital platforms like Instagram, Facebook, TikTok, and others. Ultimately, through this mentoring, partners' businesses have significantly increased.